An assessment of current layered multicast techniques for real-time video - Ghazali, Osman; Hassan, Suhaidi (2004)
The deployment of real-time video applications in the Internet has increased tremendously in recent years, and at the same time Layered Multicast Protocol (LMP) has achieved similar attention in the research community. Since LMP is regarded as one of the solution for real-time video applications, this paper attempts to assess the techniques employed in the current LMPs. We present a taxonomy of layered multicast techniques as well as the analysis of each facet of the taxonomy. Finally some research issues are highlighted.